1999
DOI: 10.1046/j.1442-9993.1999.00946.x
|View full text |Cite
|
Sign up to set email alerts
|

Fire regime, fire intensity and tree survival in a tropical savanna in northern Australia

Abstract: Dry season fires are a feature of the tropical savannas of northern Australia. As part of a landscape‐scale fire experiment, we examined the effects of fire regimes on tree survival in a tropical savanna in Kakadu National Park, northern Australia. The fire regimes were annual early dry season (June) fires, annual late dry season (September) fires, and, no fire (control). Prescriptive, experimental fires were lit annually, between 1990 and 1994, in replicate compartments, each 15–20 km2. In addition to the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
351
2
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(386 citation statements)
references
References 29 publications
27
351
2
6
Order By: Relevance
“…There must be other aspects of bark or stem anatomy that facilitate the success of the eucalypts and the escape height strategy in general. Tropical savannas worldwide have been under selection pressure from fire for much of their evolutionary history (Bond and Van Wilgen 1996, Gill 1997, Williams et al 1999, Bowman 2000. Accordingly, the dominant tree families in these savannas, for example the Myrtaceae (eucalypts) in Australia, display unique adaptations to fire that optimise the protective function of the bark and facilitate epicormic resprouting and comparatively rapid recovery from fires of low to moderate intensity .…”
Section: Discussionmentioning
confidence: 99%
“…There must be other aspects of bark or stem anatomy that facilitate the success of the eucalypts and the escape height strategy in general. Tropical savannas worldwide have been under selection pressure from fire for much of their evolutionary history (Bond and Van Wilgen 1996, Gill 1997, Williams et al 1999, Bowman 2000. Accordingly, the dominant tree families in these savannas, for example the Myrtaceae (eucalypts) in Australia, display unique adaptations to fire that optimise the protective function of the bark and facilitate epicormic resprouting and comparatively rapid recovery from fires of low to moderate intensity .…”
Section: Discussionmentioning
confidence: 99%
“…Russell-Smith et al 1997, 2003Yates et al 2008;Price et al 2012 Price et al (2012) showed that mean fire extent in the LDS period was reduced by 16.5% by comparison with the mean extent for the prior 15 years, yielding a mean overall reduction of 6%. Reduction in the extent and severity of LDS fires is known to have significant benefits both for obligate seeders and resprouting species (Williams et al , 1999Russell-Smith et al 2002b.…”
Section: Discussionmentioning
confidence: 99%
“…Monsoonal rains in the wet season result in a short, but rapid, period of vegetation production. The cessation of rain following the wet season and the extended dry season leads to a sharp decrease in the available nutrients in this vegetation, but also to an increase in its flammability due to drying (Williams et al 1999). Subsequently, many habitats burn due to direct humancaused fires or lightning strikes associated with frequent storms in the later dry season (Williams et al 2004).…”
Section: Study Regionmentioning
confidence: 99%